“Efl teaching-learning process of a student with autism spectrum disorder” - Pillajo Mejia, Damaris Slendy (2023)
Currently, the rate of children diagnosed with Autism Spectrum Disorder (ASD) has been increasing. It is very common to see this type of student immersed in the regular educational system (Hashim et al., 2021). Therefore, this qualitative research with a descriptive approach has as objective to analyze the EFL teaching-learning process of a student with Autism Spectrum Disorder. A semi-structured interview, a semi-structured observation sheet and field notes were used as data collection instruments. Two English teachers participated in this research who were interviewed in order to identify their challenges and opinions about the EFL teaching-learning process. An autistic student with a degree of 58% of the spectrum also participated. The researchers observed him to identify his challenges and strengths during four English classes. The results of this study reflected that English teachers and autistic students have to face challenges during the teaching-learning process. The main challenges that teachers face are the degree of complexity of the ASD in the student, the poor teacher training, and the design of didactic material. While the challenges the student faces have to do with lack of socialization and communication, and teachers' negative opinions about the importance of teaching English. Despite this, the autistic student has strengths such as his good memory, his visual strength, and mainly he is not afraid of making mistakes and shows a good attitude towards learning English, proving to be a good learner of the language. Finally, EFL teachers expressed their opinions on what the Government should do to support the EFL teaching-learning process of an autistic student. They mainly mentioned the compliance with public policies, and the incorporation of special education as a subject in pedagogy careers.